2012
DOI: 10.1074/jbc.m112.419283
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Localization of the α and β Subunits and of the II-III Loop in the Skeletal Muscle L-type Ca2+ Channel

Abstract: Background:The 3D molecular structure of the L-type channel is poorly understood. Results: The 3D locations of the ␣ and ␤ subunits and the II-III loop are identified. Conclusion: Key membrane targeting and signal transduction elements are placed in the context of the channel and cell membrane. Significance: This work provides novel insight in the L-type channel structure-function relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 71 publications
2
22
0
1
Order By: Relevance
“…2F), engineered at 1a's N terminus. 25 This localization is compatible with previous antibody labeling. 29,30 The atomic structure of the core region of the 2a isoform, encompassing the Src Homology 3 (SH3) domain and a guanylate kinase (GK) domain, 35 with 84% identity with 1a, was docked into the 3D reconstruction of the DHPR complex obtained by TEM taking several factors into account.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…2F), engineered at 1a's N terminus. 25 This localization is compatible with previous antibody labeling. 29,30 The atomic structure of the core region of the 2a isoform, encompassing the Src Homology 3 (SH3) domain and a guanylate kinase (GK) domain, 35 with 84% identity with 1a, was docked into the 3D reconstruction of the DHPR complex obtained by TEM taking several factors into account.…”
supporting
confidence: 74%
“…The 3D structures of skeletal DHPR that have remained consistent with the increase in resolution 25,29,30 show a main globular body with an appendage emerging from it. The structural description will be centered in our negative staining 3D reconstruction, which has the highest resolution to date (19 Å) and enabled placing of the 1s and 1a subunits for the first time.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…1, top right). Ahead of the latter structure, Szpyt et al (2012) presented a lower resolution structure (∼19 Å) that identified many components of the Ca V 1.1 channel complex. The crystal structure of the Na V Ab bacterial Na + channel (Payandeh et al, 2011) was used to estimate the position and orientation of the α 1S subunit with the cryo-EM structure.…”
Section: Introductionmentioning
confidence: 99%